Risk Factors in Normal-Tension Glaucoma and High-Tension Glaucoma in relation to Polymorphisms of Endothelin-1 Gene and Endothelin-1 Receptor Type A Gene. (1st December 2015) - Wróbel-Dudzińska, Dominika; Kosior-Jarecka, Ewa; Łukasik, Urszula; Kocki, Janusz; Witczak, Agnieszka; Mosiewicz, Jerzy; Żarnowski, Tomasz
Abstract : The aim of the research is to analyse the influence of polymorphisms of endothelin-1 gene and endothelin-1 receptor type A gene on the clinical condition of patients with primary open angle glaucoma. Methods . 285 Polish patients took part in the research (160 normal-tension glaucoma and 125 high-tension glaucoma). DNA was isolated by standard methods and genotype distributions of four polymorphisms in genes encoding endothelin-1 (K198N) and endothelin-1 receptor type A polymorphisms (C1222T, C70G, and G231A) were determined. Genotype distributions were compared between NTG and HTG groups. The clinical condition of participants was examined for association with polymorphisms. Results . A similar frequency of occurrence of the polymorphic varieties of the studied genes was observed in patients with NTG and HTG. There is no relation between NTG risk factors and examined polymorphisms. NTG patients with TT genotype of K198N polymorphism presented with the lowest intraocular pressure in comparison to GG + GT genotype (p = 0.03 ). In NTG patients with CC genotype of C1222T polymorphism (p = 0.028 ) and GG of C70G polymorphism (p = 0.03 ) the lowest values of mean blood pressure were observed. Conclusions . The studied polymorphic varieties (K198N, C1222T) do have an influence on intraocular pressure as well as arterial blood pressure in NTG patients.